MSME DEVELOPMENT MODEL IN CONVENTIONAL BANKS IN MEDAN CITY - Sri Fitri Wahyuni; Muhammad Shareza Hafiz; Riyan Pradesyah (SEAN Institute, 2023)
Study This aim for see influence role, contribution, quality of human resources, to MSME development in the city of Medan, with capital as intervening variable. Study This carried out in the city of Medan, and which became target in study is community that has incoming business category in MSMEs. Method used with approach quantitative, with tool analysis SmartPLS. As for the results obtained, Role has influence in a manner No direct to MSME development, with capital as intervening variable. this proven with mark P Values of 0.012 <0.05. Contribution No own influence in a manner No direct to MSME development, with capital as intervening variable. this proven with mark P Values of 0.606 > 0.05. HR quality is not own influence in a manner No direct to MSME development, with capital as intervening variable. this proven with mark P Values of 0.393 > 0.05